EFEKTIVITAS PROGRAM BANK SAMPAH SEBAGAI UPAYA PENGELOLAAN SAMPAH PADA BANK SAMPAH BALI BERSIH - Ni Komang Erika Depi Permatasari; I Wayan Sugiartana; I Komang Trisna Eka Putra (Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
Waste bank is a waste management program that encourages a community to contribute to the efforts for better environment. Community’s participation is essential to such a program. In waste management, it is commonly known that separation of non-organic waste from organic waste has to be done. However, there is still a lot of non-organic waste ending up at TPA (Final Waste Disposal). This study was conducted to reveal the effectiveness of the waste bank program and the participation of the community. The researhers collected the data through interviews in this qualitative study. The effectiveness of the waste bank was measured with four indicators –   accuracy, dissemination, objectives, and monitoring. The analysis shows that the effectiveness of this program is low. The participation of the community is also low. Many of them do not separate non-organic waste from organic waste before disposing it. The authority of Padangsambian village has to make regulations that force the villagers to sort out the waste in their houses.  The authority also has to disseminate the program more intensively so as to improve the awareness of the villagers.